COMMUNITY ENFORCEMENT TO COMMUNITY EMPOWERMENT: CASE STUDY OF CHILI COLLECTIVE MARKETING ON COASTAL SANDY LAND YOGYAKARTA SPECIAL REGION - Alia Bihrajihant Raya (UNEJ e-Proceeding, 2017)
Coastal sandy land had been assumed as marginal land and abandoned for many years.Farmers who was living on coastal sandy land of Kulon Progo District had faced the worstpoverty problem. Since 1970 to 1980, they had cultivated coastal sandy land subsistently. Allof the inhabitants could not have a good economic condition, education, and healthy. Eyedisease had been epidemic on the dry season while health facility was inaccessable. However,recently, in that coastal sandy land area has been able to produce an economical commoditysuch as chili, watermelon, papaya and other horticulture products. Technological innovationwhich discovered by a farmer changed the socio-economics condition of coastal sandy landfarmers. It was invented by the farmer who belongs to B Farmer Group (BFG). As pioneers ofchili farming on coastal sandy land, the farmers in the BFG always attempt to invent newtechnology like evolution of well for watering technology and plastic mulch to ease the mostdifficult tasks of cultivating on marginal land. Those innovations diffused to neighboringvillages, G Farmer Group (GFG). Meanwhile, the GFG enforced institutionalized land planningfor the sustainability of chili farming. Then, GFG could introduce the institutional innovationtaking advantage of shared norms as a community. Community enforcement happened on theGFG through the sanction for dishonest behavior of individual against the farmer group. Theleader takes authority control of sanction while mostly individual member awares theequality and evennes for all of members and then, they achieved chili collective marketingsuccessfully. To understand how the community enforcement is part of the way to empowerthe community, social network analysis was used to mapping the pattern of relationship. Inaddition, exponential random graph models (ERGM) was functioned to gather the structuraleffect of ties in the farmer group network. To understand the effect of leader on communityenforcement, again ERGM was used to predict the role of leaders as exogenous effects onnetwork. The result of social network pattern, interlocking network appears on the GFG,members tend to get connected each other. The connection among members happenedbecause of the social norms and social setting on the farmer group. They attempt to form thestructural equivalence then community enforcement could empower them to workcollectively. Being connected, it means community shared the knowledge and informationconformly while connectivity among leaders have influenced on the information validity.